2013
DOI: 10.1111/liv.12175
|View full text |Cite
|
Sign up to set email alerts
|

Plasma copeptin, a possible prognostic marker in cirrhosis

Abstract: In cirrhotic patients, copeptin concentrations increased along with the severity of liver disease. In our cohort, the 1-year mortality or liver transplantation was predicted by high MELD score and high concentrations of CRP and copeptin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 32 publications
8
32
0
Order By: Relevance
“…Pharmacokinetics of CPT, proADM and pro-ANP have been extensively investigated, and a long half-life may cause similar concentrations in all vascular beds [16,33,34]. We found a close correlation to creatinine levels and evidence of both CPT, proADM and proANP being extracted in the kidneys, suggesting a clearance of peptides from the kidneys, previously described by Moreno et al [35]. The high levels of CPT could also be explained merely by a higher release of the peptide in patients with renal dysfunction.…”
Section: Haemodynamicssupporting
confidence: 86%
“…Pharmacokinetics of CPT, proADM and pro-ANP have been extensively investigated, and a long half-life may cause similar concentrations in all vascular beds [16,33,34]. We found a close correlation to creatinine levels and evidence of both CPT, proADM and proANP being extracted in the kidneys, suggesting a clearance of peptides from the kidneys, previously described by Moreno et al [35]. The high levels of CPT could also be explained merely by a higher release of the peptide in patients with renal dysfunction.…”
Section: Haemodynamicssupporting
confidence: 86%
“…In France, 123 consecutive patients were recruited from September 2011 till June 2012. Details on this cohort have been recently reported . Serum samples for copeptin measurement were drawn at hospital admission for either elective screening for LT or for acute decompensation of cirrhosis.…”
Section: Methodsmentioning
confidence: 99%
“…However, only a few studies have assessed the association between serum copeptin concentration and haemodynamic changes in cirrhotic patients . So far, one study investigated the prognostic significance of copeptin in the setting of cirrhosis using a combined endpoint of death or liver transplantation (LT) . In the present study, we aim to investigate whether copeptin is of prognostic significance on transplant‐free survival in cirrhosis, independently of clinical parameters and liver‐specific prognostic scores.…”
mentioning
confidence: 99%
“…e measurement of vasopressin is difficult, but copeptin is more stable and easier to be detected in the blood. Moreno et al [38] reported that plasma copeptin levels were increased along with the severity of liver disease in cirrhotic patients, with a 2.3-fold risk of death/liver transplantation in high-level patients compared with low-level ones, and independently predicted the 1-year mortality or liver transplantation (AUROC: 0.7). Kerbert et al [39] investigated 61 LC patients at the waiting list for liver transplantation and found that patients with low levels of serum copeptin had a significantly higher transplant-free survival rate than those with high levels of copeptin.…”
Section: Prognostic Biomarkers Of Survival Ratementioning
confidence: 99%